2006
DOI: 10.1093/her/cyl060
|View full text |Cite
|
Sign up to set email alerts
|

The impact of including husbands in antenatal health education services on maternal health practices in urban Nepal: results from a randomized controlled trial

Abstract: Observational studies suggest that including men in reproductive health interventions can enhance positive health outcomes. A randomized controlled trial was designed to test the impact of involving male partners in antenatal health education on maternal health care utilization and birth preparedness in urban Nepal. In total, 442 women seeking antenatal services during second trimester of pregnancy were randomized into three groups: women who received education with their husbands, women who received education… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

22
288
7
5

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 305 publications
(322 citation statements)
references
References 35 publications
22
288
7
5
Order By: Relevance
“…Health professionals do not expect them to come, do not encourage them and may have negative perceptions of men’s involvement [13,25]. Numerous studies have also indicated the barriers that men face in accessing health services for themselves and becoming engaged with services during pregnancy and childbirth [1,26,34,38]. Policies and programs should take into consideration these societal barriers if they want to enhance men’s engagement during this period.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Health professionals do not expect them to come, do not encourage them and may have negative perceptions of men’s involvement [13,25]. Numerous studies have also indicated the barriers that men face in accessing health services for themselves and becoming engaged with services during pregnancy and childbirth [1,26,34,38]. Policies and programs should take into consideration these societal barriers if they want to enhance men’s engagement during this period.…”
Section: Discussionmentioning
confidence: 99%
“…Men play an important role in women’s and children’s health [13]. Studies have primarily focused on the negative impact of men’s behavior on women’s health, e.g.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Men and the socio-cultural construction of masculinities are now recognised to have important implications for women's reproductive health outcomes (Mullany, Becker and Hindin, 2007), however, research based within the autonomy paradigm seems unlikely to produce a full understanding of these complex influences.…”
Section: Men's Involvement In Women's Reproductive Health Issuesmentioning
confidence: 99%